DETERMINING OPTIMUM CAPITAL STRUCTURE (CASE STUDY: PT MMS) - Hapsari, Rr. Amirah Puspita; Sudrajad, Oktofa Yudha (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study analyzes the optimal capital structure for PT MMS, a high-precision steel cutting service company using EDM wire technology. From 2019 to 2024, the company operated without long-term debt, reflecting a conservative but potentially underleveraged position. Using a descriptive quantitative approach with embedded mixed methods, data were gathered from financial reports, customer surveys, and internal interviews. The analysis covered financial performance (profitability, liquidity, activity) and organizational environment (PESTEL, Porter's Five Forces, SWOT). Capital structure optimization was conducted through WACC simulations, with the cost of equity estimated via CAPM and cost of debt derived synthetically using the Damodaran approach. Results show that the optimal capital structure is 25% debt and 75% equity, achieving the lowest projected WACC of 10.105% in 2025, compared to 11.05% under a 100% equity scenario. A high Interest Coverage Ratio (ICR) of 19.21 further supports the firm’s capacity to adopt debt financing. However, since the firm’s ROC and ROE remain below its capital costs, moderate leverage should only be implemented once project returns improve to ensure value creation.